Dynamic amplification factor for torsional effects according to tbe Covenin 1756-82 code - Arias Alban, Gustavo (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
The Venezuelan seismic building code (Covenin 1756 - 82) stipulates the use of dynamics amplification factors applied to torsional effects, but does not derive the values of these factors by means of formulae or analytical methods. A calculation procedure for these factors, based on a modal analysis of single-story buildings with a single axis of symetry in its plant and movement perpendicular to this axis, is presented. The intent of this method is to facilitate the application of the code provisions by means of a simple procedure which can be included in any conventional seismic analysis program.